2019
DOI: 10.1145/3359281
|View full text |Cite
|
Sign up to set email alerts
|

Head-mounted Displays, Smartphones, or Smartwatches? -- Augmenting Conversations with Digital Representation of Self

Abstract: Technologies that augment face-to-face interactions with a digital sense of self have been used to support conversations. That work has employed one homogenous technology, either 'off-the-shelf' or with a bespoke prototype, across all participants. Beyond speculative instances, it is unclear what technology individuals themselves would choose, if any, to augment their social interactions; what influence it may exert; or how use of heterogeneous devices may affect the value of this augmentation. This is importa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Further design considerations will need to be developed for users of situated visualisation applications to keep them safe from potential dangers that may arise due to distraction. Social considerations also may also arise from how application use affects others in the user's vicinity [64]. Supporting safe and social applications will require integration of contextual awareness [57] with adaptive systems [85].…”
Section: C5: Applying Spatial Visualisation Ethicallymentioning
confidence: 99%
“…Further design considerations will need to be developed for users of situated visualisation applications to keep them safe from potential dangers that may arise due to distraction. Social considerations also may also arise from how application use affects others in the user's vicinity [64]. Supporting safe and social applications will require integration of contextual awareness [57] with adaptive systems [85].…”
Section: C5: Applying Spatial Visualisation Ethicallymentioning
confidence: 99%
“…Digital technologies have enabled adding a virtual layer around the human body, creating a digital aura. Using augmented reality (AR) techniques, the aura can be visible to others using digital viewers, such as head-mounted displays (HMD), smartphones, and smartwatches or projected into the physical world (Hirskyj-Douglas et al, 2019). Genç et al (2018) highlighted "extending the expression of the garments to the environment" as a design opportunity for augmenting human appearances.…”
Section: Digital Auramentioning
confidence: 99%
“…The user takes a turn with a partner that is invisible to his human partners. A comparative study [30] on making profile information available on a smartphone, a smartwatch, or smart glasses concluded that for support of conversations, participants preferred a smartphone or a smartwatch that could be used for screen sharing, while from a privacy point of view the preference was given to the glasses. It should be noted, however, that this study concerned profile information only.…”
Section: Figure 1 Google Glass With Face Recognitionmentioning
confidence: 99%